Stressing state characteristics of reinforcement concrete box-girders strengthened with carbon fiber reinforced plastic - Xiao, Hengheng; Shi, Jun; Liu, Junran; Zheng, Kaikai; Zhou, Guangchun (Journal of Civil Engineering and Management, 2020)
This paper investigates structural performance of five reinforcement concrete (RC) box-girders under a combination loading of bending, shear and torsion, applying the structural stressing state theory. The measured strain data is modeled as generalized strain energy density (GSED) to characterize the structural stressing state mode. Then the Mann-Kendall (M-K) criterion is innovatively applied to detect the leap characteristics of RC box-girders’ stressing state from the E’-T curves, deriving the new definition of structural failure load. Furthermore, the reinforcement effects of different Carbon Fiber Reinforced Plastic (CFRP) wrapping schemes on the behaviors of experimental RC box-girders are revealed through comparing strain modes of stirrup and longitudinal reinforcement. Finally, the method of numerical shape function is applied to reasonably expand the limited strain data for further exploring the strain distribution of cross section and analyzing the stressing state characteristics of the RC box-girders. The research results provide a new angle of view to conduct structural analysis and a reference to the improvement of reinforcement scheme. First published online 29 November 2019